PONDOK PESANTREN SALAF TRANSFORMATIF SEBUAH ANALISIS FUTUROLOGIS KEBUTUHAN MASYARAKAT ERA GLOBALISASI - Mohammad Arif (LPPM Institut Agama Islam Al-Hikmah Tuban, 2011)
Abstract : Muslim boarding school of salaf is part of macro society. What has connection with development and social change what is happen in this era. Muslim boarding school of salaf is an institution what inherit and protect continuity islamic tradition what is developed by 'ulama from era to era, it isn't limited to special period in islamical history. Social life pattern of salaf muslim boarding school still appears value combine three elements, named worshipping for iman entering, tablig for iman dissemination, science and deed for realiting diary activity in the social life. Ideal salaf muslim boarding school this era is salaf muslim boarding school what constant defending salaf tradition and values, but can answer, give problem solving and needed by society namely transformative salaf muslim boarding school.